PENGARUH PAPARAN INFORMASI COVID-19 TERHADAP INTENSI PANIC BUYING MELALUI KECEMASAN MAHASISWA KOTA BANDUNG - Irsan, Dimas Maulana; Fuady, Ikhsan; Munajat, Enjat; Arifin, Hadi Suprapto (Jurnal Studi Komunikasi dan Media, 2023)
Information is known to have an influence on the formation of attitudes and behavior. The COVID-19 information on Instagram is inseparable, which of course has an impact on the recipients. Especially during this pandemic, many people have the intention of panic buying. This raises a question that is there a possibility that the information that is spread can affect a person's attitude and behavior, especially anxiety and panic buying intentions. This research aim to build a model and find out how the influence of exposure to COVID-19 information on Instagram builds anxiety and panic buying intentions. Elaboration Likelihood Model is used as a theory with a quantitative approach and survey method here. Data collection was carried out by distributing questionnaires online to 454 sample respondents from the Bandung City student population. After the data is collected, the results are analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.9. The findings from this study are that information consisting of information quality and source credibility has a significant influence. Anxiety is also known to have a significant influence on the formation of panic buying intentions. So, information exposure has an influence on the formation of panic buying intentions through anxiety.